353 Patients with N2 Non-Small Cell Primary Lung Cancer, Does Surgery Offer an Advantage?. (19th August 2022) - Jackson, D; Badran, A
Abstract: Background: Non-small cell lung cancer (NSCLC) is one of two histological types of lung cancers. Evidence-based guidelines recommend radical resection in early-stage lung cancer, N2 disease is when there is moderately advanced lymph node spread of the cancer, recommendations for surgery at this stage are more contested. Aim: This was a service evaluation of the management of patients with NSCLC N2 disease. We aimed to evaluate the management and outcomes of these patients to see whether surgery offers an advantage over other modalities. Method: This was a retrospective cohort study reviewing patients treated at University Hospital Southampton (UHS) who were diagnosed with N2 NSCLC before the start of treatment from 2016–2018 and comparing survival of surgically managed patients with those treated in other ways. Results: 50 N2 patients were included, 32 had radical treatment and 11 of these underwent surgery. Kaplan-Meier survival analysis showed no significant statistical difference (Log rank = 2.342 p = 0.679) between surgery and other treatments, the survival plots showed a slightly better initial survival for chemoradiotherapy. Men were statistically more likely to have squamous cell carcinomas than women who had more adenocarcinomas. PS was shown to have significant effect on survival with higher PS having a worse survival. Conclusions: We didn't find a statistically significant difference in the survival between patients managed surgically and other modalities. PS's effect on survival reiterates its importance when deciding on treatments to offer patients.